An Overview Of B- Cell Lymphoma Subtypes and Their Classification - Laila M Abdelrahim; Hanan F Hiblo; Asma M Abdelrahim 3 (Libyan Journal of Medical and Applied Sciences, 2025)
B-cell lymphomas are a heterogeneous group of malignancies derived from B lymphocytes, exhibiting diverse clinical, morphological, immunophenotypic, and genetic features, classified according to lineage, stage of differentiation. The most widely used classification systems, such as the World Health Organization (WHO) and the International Consensus Classification, are regularly updated to reflect advances in molecular and genetic understanding. B-cell lymphomas represent the majority of non-Hodgkin lymphomas (NHLs) and can occasionally present in the oral cavity, often posing diagnostic challenges due to their mimicry of benign odontogenic or inflammatory lesions. This review synthesizes current literature and World Health Organization (WHO) hematolymphoid neoplasm classifications (5th edition, 2022) to summarize key B-cell lymphoma subtypes encountered in the oral and maxillofacial region. B-cell lymphoma classification is increasingly driven by molecular and genetic insights, Genetic subtyping guides targeted therapy and predicts response to immunochemotherapy, especially in DLBCL with the WHO-5 and ICC systems providing updated frameworks. Accurate subtyping is essential for prognosis and treatment, but some areas remain under active investigation as new discoveries continue to refine the field. Despite these advances, challenges remain in subclassifying certain entities and in translating molecular findings into routine clinical practice. Ongoing research and consensus efforts continue to shape the evolving landscape of B-cell lymphoma classification, aiming to enhance personalized management and therapeutic outcomes for affected patients.